INHERITANCE LAW IN THE PERSPECTIVE OF CUSTOMARY LAW, CIVIL LAW, AND ISLAMIC LAW - Muzakir, Kahar (JURNAL RUANG HUKUM, 2023)
In order to understand the rules and intricacies of inheritance law, it is almost unavoidable to first understand some terms that are commonly encountered and known. However, there are three inheritance laws that apply in Indonesia, namely customary inheritance law, civil inheritance law, and Islamic inheritance law. Customary inheritance law is the legal rules that regulate the transmission and transition from century to century both tangible and intangible assets from generation to generation. A person becomes an heir according to civil inheritance law due to marriage and blood relations, whether legally or not. The Islamic inheritance system according to the Qur'an is actually an improvement and change from the principles of inheritance law that prevailed in Arab countries before Islam, with its patrilineal family system.